Implementasi Model Project-Based Learning (PJBL) sebagai Pembelajaran Inovatif di Sekolah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the implementation of the Project-Based Learning (PjBL) model in Indonesian language learning as an innovative approach to improving students’ quality. The focus of the research is directed toward the process of implementing PjBL, students’ responses and engagement, as well as the challenges faced by teachers during the learning process. The subject of this study is an Indonesian language teacher who is also a master’s degree student and has implemented the PjBL model in teaching grade X and XI students at SMAN 1 Banjarmasin. This research employs a descriptive qualitative method, with data collected through structured interviews with a participant who has experience in implementing the model. The results of the study indicate that the PjBL model is implemented systematically through several stages, starting from project-based activity planning to evaluation and learning reflection in order to achieve optimal outcomes. The implementation of the PjBL model has been proven to enhance students’ participation and critical thinking skills, as well as to develop collaboration and creativity among students. Learning becomes more meaningful as students are directly involved in learning activities that are relevant to real-life contexts. However, several challenges were encountered during the implementation, including limited instructional time, differences in students’ abilities, and the need for intensive teacher guidance to ensure that learning objectives are achieved optimally. Therefore, the implementation of the PjBL model can be considered an innovative learning model for improving the quality of Indonesian language learning and producing high-quality learners.